2016
DOI: 10.1080/14756366.2016.1186021
|View full text |Cite
|
Sign up to set email alerts
|

Novel dipeptidyl hydroxamic acids that inhibit human and bacterial dipeptidyl peptidase III

Abstract: Human dipeptidyl peptidase III (hDPP III), a zinc-metallopeptidase of the family M49, is an activator of the Keap1-Nrf2 cytoprotective pathway involved in defense against oxidative stress. Pathophysiological roles of DPP III have not been elucidated yet, partly due to the lack of specific inhibitors. We showed that substrate analog H-Tyr-Phe-NHOH is a strong competitive inhibitor of hDPP III, while H-Tyr-Gly-NHOH expresses much weaker inhibition. To investigate the effects of amino acid substitutions in inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…36 Tyr286 is 100% conserved within the M49 family and is presumed to be a part of the S1 active subsite. 37 Both experimental 38…”
Section: The Role Of Ser340 and Tyr386mentioning
confidence: 99%
See 1 more Smart Citation
“…36 Tyr286 is 100% conserved within the M49 family and is presumed to be a part of the S1 active subsite. 37 Both experimental 38…”
Section: The Role Of Ser340 and Tyr386mentioning
confidence: 99%
“…In the experimentally determined 'closed' structure of the Bt.DPP III this distance is 22.2 Å. During the MD simulations resulting with the protein closure Tyr286 forms hydrogen bonds with Lys468, Gly461 and, most notably, Ser472 which is thought to be a part of the S2 subsite 37.…”
mentioning
confidence: 99%
“…The K m values for hydrolysis of uorogenic substrate Arg 2 -2NA were determined at pH 7.4 (20 mM Tris-HCl buffer) and at 25 C, from the initial reaction rates as previously described. 26 Under the conditions used, the K m values were 6.0 mM, 12 mM and 0.8 mM for human, yeast, and B. thetaiotaomicron DPP III, and 0.3 mM, 15.9 mM and 23.8 mM for Porphyromonas gingivalis, Caldithrix abyssi and Physcomitrella patens enzyme, respectively.…”
Section: Determination Of Kinetic Parametersmentioning
confidence: 87%
“…Detailed expression protocols were described elsewhere. 8,12,25,26,33 Protein purity was conrmed by SDS-PAGE according to Laemmli. 34 Protein concentrations were determined by the Bradford method.…”
Section: Heterologous Expression and Puricationmentioning
confidence: 99%
“…Although previous studies have shown that some pentapeptides and heptapeptide spinorphin potently inhibit mammalian DPP III, it has been reported that peptidic inhibitors are degraded in the human body by (amino) peptidases . More recent studies of the effect of dipeptide derivatives of hydroxamic acid on the human and bacterial DPP III have shown that these compounds competitively inhibit the enzyme . We have investigated and reported the inhibitory effect of benzimidazole derivatives against DPP III from human erythrocytes and found the key features responsible for their inhibitory activity .…”
Section: Introductionmentioning
confidence: 97%